Angiotensin II Stimulates the Proliferation and Migration of Lymphatic Endothelial Cells Through Angiotensin Type 1 Receptors - Lin, Qiu-Yue; Bai, Jie; Liu, Jin-Qiu; Li, Hui-Hua (Frontiers in Physiology, 2020)
Background/Aim: The proliferation and migration of lymphatic endothelial cells (LECs) is essential for lymphatic vessel growth (also known as lymphangiogenesis), which plays a crucial role in regulating the tissue fluid balance and immune cell trafficking under physiological and pathological conditions. Several growth factors, such as VEGF-C, can stimulate lymphangiogenesis. However, the effects of angiotensin II (Ang II) on the proliferation and migration of mouse LECs and the underlying potential mechanisms remain unknown. Methods: Wild-type mice were infused with Ang II (1000 ng/kg/min) for 1 to 2 weeks. Murine LECs were stimulated with Ang II (500 nM) or saline for 12 to 48 hours. Cell proliferation was determined with 5-bromo-2-deoxyuridine (BrdU) incorporation assays, while cell migration was assessed by scratch wound healing and transwell chamber assays. The gene expression profiles were obtained by time series microarray and real-time PCR analyses. Results: Ang II treatment significantly induced lymphangiogenesis in the hearts of mice and the proliferation and migration of cultured LECs in a time-dependent manner. This effect was completely blocked by losartan, an angiotensin II type 1 receptor (AT1R) antagonist. The microarray results identified 1,385 differentially expressed genes (DEGs) at one or more time points in the Ang II-treated cells compared with the control saline-treated cells. These DEGs were primarily involved in biological processes and pathways, including sensory perception of smell, the G protein coupled receptor signaling pathway, cell adhesion, olfactory transduction, Jak-STAT, alcoholism, RIG-I-like receptor and ECM-receptor interaction. Furthermore, these DEGs were classified into 16 clusters, 7 of which (Nos. 13, 2, 8, 15, 7, 3 and 12, containing 586 genes) were statistically significant. Importantly, the Ang II-induced alterations the expression of lymphangiogenesis-related genes were reversed by losartan. Conclusion: The results of the present indicate that Ang II can directly regulate the proliferation and migration of LECs through AT1R in vivo and in vitro, which may provide new potential treatments for Ang II-induced hypertension and cardiac remodeling. Keywords: Angiotensin II, Lymphatic endothelial cells, Proliferation, Migration, Microarray, Time-series gene expression profiling.